2014
DOI: 10.1097/pap.0000000000000030
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Dendritic Cell Pattern in Early Lymphomas Involving Follicles

Abstract: This article reviews the most typical follicular dendritic cell (FDC) patterns displayed by early lymphomas involving follicles. In in situ follicular lymphoma, FDCs form a well-developed round (spherical) dendritic meshwork with a sharp outline. Other patterns that can be seen include contracted/distorted/disintegrated FDC meshworks. In early mantle cell lymphoma with mantle zone pattern, FDCs compose an ill-outlined and loosely arranged "centrifugal" meshwork. In marginal zone lymphoma, the FDC meshwork form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A previous study has demonstrated that FDCs are closely associated with the residency and proliferation of tumor cells in follicle-derived lymphomas, even when the in ltration localizes in the bone marrow and non-lymphoid organs [28]. Moreover, another study has demonstrated that the precursors of FDCs are perivascular cells and can develop into mature FDCs under certain conditions [12], which indicates that FDCs may not restrict in the lymphatic organ.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has demonstrated that FDCs are closely associated with the residency and proliferation of tumor cells in follicle-derived lymphomas, even when the in ltration localizes in the bone marrow and non-lymphoid organs [28]. Moreover, another study has demonstrated that the precursors of FDCs are perivascular cells and can develop into mature FDCs under certain conditions [12], which indicates that FDCs may not restrict in the lymphatic organ.…”
Section: Discussionmentioning
confidence: 99%
“…FDC's main functions comprise: histoarchitecture organization of lymphoid follicles, antigen trapping and presentation, organization of apoptotic "waste" removing, and self-immunity prevention. Organizing functions of FDCs are chemokine dependent (Carbone and Gloghini 2014). B-cell lymphomas of follicular origin: classification B-cell lymphomas of presumed follicular origin include follicular lymphoma (FL), mantle cell lymphoma (MCL) and marginal zone lymphoma (MZL).…”
Section: Clinics and Pathologymentioning
confidence: 99%
“…The FDC meshwork usually form a well-developed "spherical" dendritic meshwork with a sharp outline highlighting an attenuated mantle zone (Figure 1). Other patterns that can be seen include contracted/distorted/disintegrated FDC meshworks (Rezk et al, 2013;Carbone and Gloghini 2014).…”
Section: Follicularlymphomamentioning
confidence: 99%
See 2 more Smart Citations